Neuromuscular Junction Impairment in Amyotrophic Lateral Sclerosis: Reassessing the Role of Acetylcholinesterase - Campanari, Maria-Letizia; García-Ayllón, María-Salud; Ciura, Sorana; Sáez-Valero, Javier; Kabashi, Edor (Frontiers in Molecular Neuroscience, 2016)
Amyotrophic Lateral Sclerosis (ALS) is a highly debilitating disease caused by progressive degeneration of motorneurons (MNs). Due to the wide variety of genes and mutations identified in ALS, a highly varied etiology could ultimately converge to produce similar clinical symptoms. A major hypothesis in ALS research is the “distal axonopathy” with pathological changes occurring at the neuromuscular junction (NMJ), at very early stages of the disease, prior to MNs degeneration and onset of clinical symptoms. The NMJ is a highly specialized cholinergic synapse, allowing signaling between muscle and nerve necessary for skeletal muscle function. This nerve-muscle contact is characterized by the clustering of the collagen-tailed form of acetylcholinesterase (ColQ-AChE), together with other components of the extracellular matrix and specific key molecules in the NMJ formation. Interestingly, in addition to their cholinergic role AChE is thought to play several ‘non-classical’ roles that do not require catalytic function, most prominent among these is facilitation of neurite growth, NMJ formation and survival. In all this context, abnormalities of AChE content have been found in plasma of ALS patients, in which AChE changes maybe reflect the neuromuscular disruption. We review these findings and particularly the evidences of changes of AChE at neuromuscular synapse in the pre-symptomatic stages of ALS.